Health-related quality of life among spondyloarthritis and chronic low back pain patients: results from a nationwide population-based survey - Santos, H (2022)
Purpose: Both spondyloarthritis and chronic low back pain (CLBP) significantly impact health-related quality of life (HRQoL). It is important to clarify whether these disorders have different impacts on the several domains of HRQoL as different mechanisms may necessitate different treatment interventions. Moreover, the factors associated with HRQoL can inform more targeted group interventions to promote HRQoL. Methods: We used data from EpiReumaPt, a population-based survey conducted from September 2011 to December 2013. HRQoL was assessed with EuroQoL-5-Dimensions (EQ-5D). Spondyloarthritis was diagnosed by expert opinion (rheumatologist) and predefined criteria. CLBP was diagnosed if low back pain was present on the day of the interview and persisted for > 90 days. Univariable and multivariable linear regression analyses compared HRQoL among subjects with spondyloarthritis, CLBP, and no rheumatic diseases. Multivariable linear regression analyses evaluated HRQoL factors in spondyloarthritis and CLBP subjects. Results: We included 92 spondyloarthritis patients, 1376 CLBP patients, and 679 subjects without rheumatic diseases. HRQoL was similarly affected in spondyloarthritis and CLBP (ß = - 0.03, 95% CI [- 0.08; 0.03]) in all EQ5D dimensions. A much lower HRQoL was found in spondyloarthritis and CLBP patients compared with subjects without rheumatic diseases (ß = - 0.14, 95% CI [- 0.19; - 0.10]; ß = - 0.12, 95% CI [- 0.14; - 0.09], respectively). In spondyloarthritis subjects, multimorbidity and active disease were associated with worse HRQoL (ß = - 0.18; 95% CI [- 0.24; 0.03]; ß = - 0.13; 95% CI [- 0.29; - 0.05], respectively), and regular physical exercise was associated with better HRQoL (ß = 0.18; 95% CI [0.10; 0.30]). In CLBP subjects, multimorbidity (β = - 0.11; 95% CI [- 0.14; - 0.08]), obesity (β = - 0.04; 95% CI [- 0.08; - 0.01]), and low back pain intensity (β = - 0.02; 95% CI [- 0.03; - 0.02]) were associated with worse HRQoL, and regular physical exercise (β = 0.08; 95% CI [0.05; 0.11]) was significantly associated with better HRQoL. Conclusion: Spondyloarthritis and CLBP subjects reported similar levels of impairment in the mental, physical, and social domains of HRQoL. Future health plans should address modifiable factors associated with HRQoL in these conditions to achieve better outcomes.